Comparative study of condylar inclination settings in two types of semiadjustable articulators - Žabarović, Domagoj (Array, 2009)
Abstract: The purpose of this study was to research the possible influence of difference in construction of mechanical joint in arcon and nonarcon articulators, upon the adjustment of condylar inclination by intraoral protrusive record. The determination of condylar inclination by protrusive record in two types of articulators was performed on 30 examinees, and the adjustment of condylar inclination in each articulator was done for left and right joint. In arcon articulator the measured values for condylar inclination were higher and the mean difference for right joint was 7.4°, and for the left joint 7.2° The found differences are statistically significant for both, left and right joint, at the level of P<0.001. There is possible influence of difference in construction of mechanical joint upon the adjustment of condylar inclination by intraoral protrusive record. The arcon articulator, due to constant relation between occlusal plane and mechanical fossa, reproduces the movements more accurately